2019
DOI: 10.3892/mmr.2019.10774
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine improves cardiac function and protects against maladaptive remodeling following myocardial infarction

Abstract: Dexmedetomidine (DEX), a highly specific and selective α2 adrenergic receptor agonist, has been demonstrated to possess potential cardioprotective effects. However, the mechanisms underlying this process remain to be fully illuminated. In the present study, a myocardial infarction (MI) animal model was generated by permanently ligating the left anterior descending coronary artery in mice. Cardiac function and collagen content were evaluated by transthoracic echocardiography and picrosirius red staining, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…To investigate the cardioprotective effects of DEX against MI/RI, we established a mouse model of MI/RI to assess cardiac function and infarct sizes. Consistent with previous reports [33], the DEX-administered group exhibited preserved left ventricular systolic function compared to the vehicle-treated group subjected to MI/RI, as monitored by cardiac ultrasound (Fig. 1A-B).…”
Section: Dex Protects Against Mi/ri Via Promoting Ibatreleased Fgf21supporting
confidence: 91%
See 1 more Smart Citation
“…To investigate the cardioprotective effects of DEX against MI/RI, we established a mouse model of MI/RI to assess cardiac function and infarct sizes. Consistent with previous reports [33], the DEX-administered group exhibited preserved left ventricular systolic function compared to the vehicle-treated group subjected to MI/RI, as monitored by cardiac ultrasound (Fig. 1A-B).…”
Section: Dex Protects Against Mi/ri Via Promoting Ibatreleased Fgf21supporting
confidence: 91%
“…Besides, other studies have revealed that DEX preconditioning protects the hearts against I/R injury via alleviating myocardial in ammation and apoptosis [41], downregulation of the endoplasmic reticulum stress signaling pathway [42],or exerting antioxidant stress through the activation of the Keap1/Nrf2/ARE signal pathway [43]. In particular, DEX pretreatment prevents maladaptive remodeling from myocardial infarction [33].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we evaluated the effect of PAGln on atrial myocytes. Compared with the control group, PAGln (100 μM, 24 h) intervention significantly increased ROS generation (1.44 ± 0.18 vs. 0.80 ± 0.17 fold change; p = 0.011), NOX activity, a major source of excess ROS in the cardiovascular system [ 24 ], and apoptosis (56.25 ± 1.18 vs. 49.76 ± 0.93%, p = 0.002) in mouse HL-1 cells ( Figure 4 A–C). Moreover, treating HL-1 cells with PAGln for 24 h induced a striking decrease in SOD activity, a myocardial endogenous antioxidant [ 24 ], and the MTT values ( Figure 4 D,E), showing that PAGln could dramatically impair atrial myocyte viability.…”
Section: Resultsmentioning
confidence: 99%
“…AST, CK-MB, cTnl, and LDH are common factors that can reflect myocardial function damage. Dex and PPF are known to have cardioprotective effects according to previous research[ 36 , 41 ]. In the present study, Dex or/and PPF down-regulated the levels of cTnl, CK-MB, AST, and LDH, especially Dex combined with PPF.…”
Section: Discussionmentioning
confidence: 99%